2007
DOI: 10.1073/pnas.0704185104
|View full text |Cite
|
Sign up to set email alerts
|

Labor force participation and human capital increases in an aging population and implications for U.S. research investment

Abstract: The aging of the U.S. labor force will continue to at least 2034, when the largest of the baby boom cohorts reaches age 70. Thus, the average health and functional capacity of persons age 65؉ must improve for sufficient numbers of elderly persons to be physically and cognitively capable of work. This will require greater investments in research, public health, and health care. We examine how disability declines and improved health may increase human capital at later ages and stimulate the growth of gross domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…1,2 Coronary artery disease prevalence rises with age, and coronary revascularization is commonly performed in elderly patients for treatment. 3 Prior studies have demonstrated a 2-to 4-fold higher risk of mortality and major complications in elderly patients This work was supported by Blue Cross Blue Shield of Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Coronary artery disease prevalence rises with age, and coronary revascularization is commonly performed in elderly patients for treatment. 3 Prior studies have demonstrated a 2-to 4-fold higher risk of mortality and major complications in elderly patients This work was supported by Blue Cross Blue Shield of Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…It is far lower than the current per annum increases for all scientific research in China (17%), which occurred over a longer period (12 years) (4). Evaluation of the level of investment in research suggests that a significantly greater, and more prolonged, investment in NIH, and indeed all, federal research would provide a greater stimulus to US economic growth (1).…”
Section: Health Time Trend and Budget Correlationsmentioning
confidence: 85%
“…Techno-physiological evolution (13) explained a slow (0.6% per annum), long-term rate of improvement in US health since the Civil War. Manton et al (1) suggested societal evolution may enhance aggregate cognitive fitness and mental function in addition to physical health-further enhancing positive economic effects. Manton's (12) arguments about the equilibrium of plastic morbidity, disability, and mortality processes, correlated with increases in NIH funding, may, in part, explain the recent acceleration of chronic disability declines at later ages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of working adults in the United States 65 years of age or older is projected to increase and surpass that of the large post-World War II baby boomers by 2010 (Manton, et al, 2007). As a result of the aging work force, the average health and functional capacity of individuals 65 years of age or older must improve sufficiently for them to be physically and cognitively capable of continuing to work.…”
Section: Aging Populationmentioning
confidence: 99%